Efeitos a longo prazo de Lee Silverman Voice Treatment no uso cotidiano da voz na doença de Parkinson - Cruz, Thalita Vitória Silva da; Silva, Hilton Justino da; Lira, Zulina Souza de (Distúrbios da Comunicação, 2019)
GUSTAFSSON JK, SÖDERSTEN M, TERNSTRÖM S, SCHALLING E. Long-term effects of Lee Silverman Voice Treatment on daily voice use in Parkinson’s disease as measured with a portable voice accumulator. Logopedics Phoniatrics Vocology, 2018,1-10.